TOPOLOGY OF ENTREPRENEURIAL UNIVERSITY: DYNAMIC DESCRIPTIVE MODEL - R. A. Zayakina (Moscow Polytechnic University, 2017)
The article continues the topological study of social networks created by universities which are engaged in entrepreneurial activities and strive to become members of industrial clusters. Certain procedures of real network design are used to build the algorithms of operations with descriptors characterizing the transformations which take place both inside the universities being an innovative ecosystem and systems with their participation. Dynamic network descriptors fall into functional descriptors that depend on the network function achievement and search descriptors that represent the network activity in searching an optimal strategy of the development. A set of characteristics inherent in the above mentioned descriptors is revealed and used for investigating the networks with participation of business-oriented universities. The article shows the qualities necessary for developing successful business-oriented strategies of the university and forming the environment favorable to entrepreneurship.